Solid‐State Optoelectronic Synapse Transistor Using a LaF3 Gate Dielectric. Issue 11 (18th August 2022) - Shi, Peng; Xing, Ruofei; Wu, Zhenfa; Wang, Dong; Xing, Yuzhi; Ge, Yufeng; Song, Houning; Qi, Chen; Wei, Lin; Yan, ShiShen; Tian, Yufeng; Chen, Yanxue
Abstract : As a new generation of core components for neuromorphic computing, optoelectronic synaptic devices have the advantages of high bandwidth and less energy consumption. They can combine the functions of visual sensing, signal processing, and memory in one device. Herein, an all‐solid‐state optoelectronic synaptic transistor using indium gallium zinc oxide (IGZO) as the channel and lanthanum fluoride (LaF3 ) as the gate dielectric is designed and fabricated. Its synaptic plasticity induced by electric and optical stimuli is investigated. LaF3 is a solid superionic conductor with plenty of mobile fluoride ions, which can be used to achieve a high on/off ratio of more than 10 5 and a low subthreshold swing less than 150 mV dec −1 in this novel synaptic transistor. Due to the ion‐trapping effect at the interface, synaptic plasticity can be achieved upon electrical stimulation. Synaptic plasticity by light pulse stimuli can also be accomplished with the assistance of the persistent photoconductivity effect in IGZO channel. Furthermore, it is found that the synaptic plasticity induced by light stimuli can be modulated by gate voltage. These results provide a new way to control synaptic function and extend the function of optoelectronic synaptic devices. Abstract : Optoelectronic synaptic transistor using a LaF3 solid‐state gate dielectric is designed and fabricated. Synaptic plasticity is achieved upon electrical stimulation due to fluoride ion‐trapping effect near the interface. Synaptic plasticity by light pulse stimuli is accomplished with the assistance of the persistent photoconductivity effect in indium gallium zinc oxide (IGZO) channel. Furthermore, synaptic plasticity can be modulated by gate voltage.